Respostas

2014-04-29T02:19:57-03:00
A) 26+6x=-2x+26   6x+2x=26-26   8x=0
b)3,5x+1=3+3,1x   3,5x-3,1x=3-1   0,4x=2  x=2      x=5
                                                                              0,4
d)13y-5=11+9y  13y-9y=11+5  4y=16  y=16      y=4
                                                                         4
e)9t-14=7t+20  9t-7t=20+14  2t=34   t= 34     t=12
                                                                      2
f)5-a-11=4a-22   -a-4a=-22+11-5  -5a=-16  5a=16   a=16 
                                                                                                5
2 3 2